Teacher beliefs and classroom performance : the impact of teacher education - Raths, James D.; McAninch, Amy Raths (Advances in teacher education., 2003)
This volume of Advances in Teacher Education is about beliefs held by teachers and addresses the important topic of teacher beliefs from a variety of disciplinary perspectives. Most of the authors who have contributed to this collection of essays assume that beliefs are propositions that are felt to be true by the person embracing them, but that do not necessarily rest on the kind of evidence that justifies the use of the term "knowledge." Teacher beliefs are an important topic because it is hypothesized that teachers and teacher candidates use them to shape the information they receive from formal teacher preparation and to direct subsequent decision-making in the classroom.